Numerical study of a heat-driven thermoacoustic refrigerator based on a time-domain lumped acoustic–electrical analogy model. (15th September 2022) - Xiao, Lei; Xu, Jingyuan; Luo, Kaiqi; Chen, Geng; Luo, Ercang
Graphical abstract: Highlights: A time-domain lumped model is proposed for the simulation of thermoacoustic systems. Onset and steady characteristics of a thermoacoustic refrigerator are investigated. Minimum onset temperature of 32.5 K has been achieved. Cooling power increased with increasing mean pressure, heating and cooling temperatures. Abstract: Thermoacoustic technology is a promising clean energy solution for the recovery of low-grade heat from renewable energy sources and waste heat. Existing methods for simulating thermoacoustic systems are inconsistent or time-consuming. In this study, a time-saving and reliable time-domain lumped acoustic–electrical analogy model is proposed to investigate the performance of thermoacoustic systems. In the proposed model, each component of a thermoacoustic system is simplified as a lumped acoustic–electrical analogy model. The nonlinear effects of both regenerator and liquid acoustic resistances in gas–liquid resonators are considered to obtain nonlinear dynamic evolution equations. Case studies were performed on a looped heat-driven thermoacoustic refrigerator for low-grade heat recovery to investigate its onset and steady characteristics. The evolutions of the oscillating pressure and volume flow rate were explored, which initially increase rapidly until reaching the saturation state. The minimum onset temperature was 32.5 K at a pressure of 2.5 MPa with hydrogen as the working gas. In addition, the influences of the mean pressure, heating temperature, and cooling temperature on the steady-state system performance with various working fluids were investigated. The results indicated that the cooling power increased significantly with increasing mean pressure, heating temperature, and cooling temperature. A higher working liquid density resulted in a lower onset temperature, lower working frequency, and larger pressure ratio. With the use of helium or hydrogen, the refrigerator performed better in terms of a lower onset temperature and a larger pressure ratio, cooling power, and coefficient of performance. The proposed model provides a new perspective and an effective approach to characterise the onset and steady characteristics of thermoacoustic systems.